The Facile Solid-Phase Synthesis of Thiazolo-Pyrimidinone Derivatives - Shuanghui Hua; Jimin Moon; Taeho Lee (Molecules)
A thiazolo-pyrimidinone derivative library was developed through a facile solid-phase synthesis method. For the reaction, the thiazolo[4,5-d]pyrimidin-7(6H)-one structure was synthesized through efficient Thorpe–Ziegler and cyclization reactions. The thiazolo[4,5-d]pyrimidin-7(6H)-one derivative library with a diversity of three had a total of four synthesis steps and 57 compounds. In addition, the yield per synthesis step was 65–97%, which was very high. The developed synthesis method and compounds will be used to find compounds with biological activity through the thiazole derivative structure–activity relationship.